The Effect of Kegel Exercise on Elderly With Urine Incontinence - Tomi Jepisa; Tri Mia Intani; Husni Husni; Wiladi Rasyid; Radian Ilmaskal (Eduvest - Journal of Universal Studies, 2022)
Various problems faced by the elderly include incontinence being the main complaint of the elderly. Urinary incontinence is the discharge of urine that is not digested by the elderly. Urinary incontinence will cause complications that can cause the elderly due to infection. One way to overcome all of this can be by doing Kegel exercises. The study used a pre-experimental design in the form of one group pretest-posttest without control. The results of the study describe the characteristics of age, gender, influencing the occurrence of urine iconentis in the elderly. The results of this study can be used as a reference in overcoming the problems of the elderly with urinary incontinence in the elderly. In addition, it is necessary to do it regularly in the elderly who experience urinary icontinasia.